Exploring the Relationship between Self-Concept and Intellectually Gifted Senior Secondary Students of Navodaya Schools - Bi, Shaila; Chauhan, Poonam (JOURNAL OF INDIAN EDUCATION, 2023)
The goal of this study is to investigate the relationship of self-concept among intellectually gifted students of the Class XI of Jawahar Navodaya Vidyalayas (JNVs). The data were analysed to test the significant differences between the self-concept scores of gifted males and females and the sample consisted of 383 students from the various district of JNVs of Uttar-Pradesh. Out of which, 90 were identified as gifted through the Raven’s Advanced Progressive Matrices. The self-concept questionnaire by Saraswat has been administered to measure self-concept. Pearson correlation coefficient and independent sample t-test were used to test the variables investigated. Results indicated that a positive non-significant relationship exists between self-concept scores and intelligence scores of gifted students. There exists no significant difference in self-concepts scores with regard to sex. Additionally, no significant differences were found to exist between the self-concepts scores of gifted with regard to their caste.